Murraya paniculata (L.) (Orange Jasmine): Potential Nutraceuticals with Ameliorative Effect in Alloxan‐Induced Diabetic Rats. (25th August 2017) - Menezes, Cicero Diego Almino; de Oliveira Garcia, Francisca Adilfa; de Barros Viana, Glauce Socorro; Pinheiro, Patricia Gonçalves; Felipe, Cícero Francisco Bezerra; de Albuquerque, Thaís Rodrigues; Moreira, Alisson Cordeiro; Santos, Enaide Soares; Cavalcante, Maynara Rodrigues; Garcia, Tatiana Rodrigues; Silva, Thiago Fonseca; Coutinho, Henrique Douglas Melo; et al.
Abstract : Orange jasmine, Murraya paniculata (Rutaceae), is a plant from India widely used in folk medicine as antinociceptive, antiinflammatory, and antioxidant. Although oral hypoglycemic agents and insulin are the mainstays of treatment of diabetes mellitus (DM), there is a significant demand for new natural products to reduce the development of diabetic complications. Alloxan‐induced diabetic rats were treated for 60 days with a hydroalcoholic extract of M. paniculata (MPE), at doses of 100, 200, and 400 mg/kg. MPE decreased glycemia and also cholesterol and triglyceride levels, starting 1 week after treatments, as compared with the same group before treatments. Glucose values were reduced toward normality after 1 week of treatment. MPE hypoglycemic effects were potentiated by glibenclamide and metformin. MPE also decreased fructosamine and glycated hemoglobin values. MPE reduced diabetes‐induced morphological alterations of the kidney, pancreas, and liver. MPE acts similarly to glibenclamide and metformin, and its glucose‐lowering action is partly a consequence of ATP‐sensitive K + channel inhibition. MPE may be a potential therapeutic alternative for the treatment of diabetes and its complications. Copyright © 2017 John Wiley & Sons, Ltd.